2008
DOI: 10.1016/j.jms.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectroscopy of isotopic vinyl cyanide, H2CCHCN, in the laboratory and in space

Abstract: a b s t r a c tThe rotational spectra of singly substituted 13 C and 15 N isotopic species of vinyl cyanide have been studied in natural abundances between 64 and 351 GHz. In combination with previous results, greatly improved spectroscopic parameters have been obtained which in turn helped to identify transitions of the 13 C species for the first time in space through a molecular line survey of the extremely line-rich interstellar source Sagittarius B2(N) in the 3 mm region with some additional observations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 31 publications
(142 reference statements)
7
81
1
Order By: Relevance
“…For a source size of 3 , this translates into a column density of 2.9 × 10 17 cm −2 , which is a factor 4 smaller than the column density we derive for the main velocity component. However, our model predicts peak line opacities of 4−6 for these transitions, which is supported by our simultaneous modeling of the 13 C isotopologues of ethyl cyanide (see Müller et al 2008). As a result, Liu et al (2001) most likely underestimated the column densities of ethyl cyanide by a factor of a few, which reconciles the single-dish and interferometric measurements and confirms that the source of ethyl cyanide emission is compact.…”
Section: Comparison To Related Speciessupporting
confidence: 82%
“…For a source size of 3 , this translates into a column density of 2.9 × 10 17 cm −2 , which is a factor 4 smaller than the column density we derive for the main velocity component. However, our model predicts peak line opacities of 4−6 for these transitions, which is supported by our simultaneous modeling of the 13 C isotopologues of ethyl cyanide (see Müller et al 2008). As a result, Liu et al (2001) most likely underestimated the column densities of ethyl cyanide by a factor of a few, which reconciles the single-dish and interferometric measurements and confirms that the source of ethyl cyanide emission is compact.…”
Section: Comparison To Related Speciessupporting
confidence: 82%
“…Quite commonly, we reach relative accuracies of 10 −8 or even slightly better (Müller & Brünken 2005;Müller et al 2007aMüller et al , 2008. Müller et al (2000) have shown that similar accuracies can be achieved for the rare isotopolog SO 17 O in a rather dense spectrum.…”
Section: Methodsmentioning
confidence: 58%
“…This species should be observable fairly readily in Galactic center sources because of the 12 C/ 13 C ratio of about 20 in these sources (Wilson & Rood 1994;Müller et al 2008). Hence, lines of the doubly substituted 13 C isotopolog should be only slightly weaker than those of CH 3 C 15 N. In fact, inspection of the 3 mm line survey of Sagittarius B2(N) obtained with the IRAM 30 m telecope (Belloche, private communication, 2008; see also Belloche et al 2009;Müller et al 2008) revealed that several 13 CH 13 3 CN lines should have S/N ratios of greater than three. However, all lines were overlapped by stronger lines, frequently belonging to the much stronger 13 CH 3 CN which has fairly similar spectroscopic parameters.…”
Section: Ch 13 3 Cnmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of this procedure for the Sgr B2(N) region have been given previously (Belloche et al 2008a(Belloche et al , 2009Müller et al 2008), whereas the model of Sgr B2(M) will be described elsewhere (Belloche et al, in preparation). Our LTE modeling assumes a very basic source structure, and the radiative transfer calculations are approximate.…”
Section: Astronomical Observations and Analysismentioning
confidence: 99%